Anomalous Effect of α, α, α‐Trifluoroacetophenone Derivatives on a Conjugated Umpolung Reaction: Enantioselective Direct Self‐Annulation of Enals Catalyzed by a Chiral Cyclophane‐type N‐Heterocyclic Carbene. Issue 2 (15th January 2013) - Ishida, Yasuhiro; Kawatsu, Kunihiro; Matsuoka, Yuki; Yamada, Kuniyo; Ikariya, Ryuichi; Sawayama, Jun; Hirao, Shotaro; Nishiwaki, Nagatoshi; Saigo, Kazuhiko
<x xml:space="preserve">Abstract</x> Do it yourself: A broadly applicable, enantioselective, direct self‐annulation of enals is presented. An N‐heterocyclic carbene derived from a chiral cyclophane‐type imidazolium salt catalyzes the self‐annulation of cinnamaldehyde derivatives to afford the corresponding γ‐butyrolactones with up to 99 % ee. The use of α, α, α‐trifluoroacetophenone derivatives as cocatalysts was essential to obtain satisfactory yields and enantioselectivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>